Romanian Students’ Perceptions of Bibliotherapy in the Educational Process - Popa, Daniela; Landoy, Ane; Repanovici, Angela (Trivent Publishing, 2018)
The use of bibliotherapy in the educational process leads to the improvement of students’ skills to use the reading process in a more efficient way, to transfer knowledge while enjoying the process. This paper aims to identify the level of familiarity of first year university students with therapeutic techniques and also the benefit discovered in them by the new generations of students. We surveyed 111 students on their perception of bibliotherapy in the educational process. A social survey questionnaire was created and administered online. The findings provide useful information for librarians and top management in libraries in order to help bring potential bookmakers closer to the digital age.